A base film used for MLCC release film and a preparation method thereof
By using ABA three-layer composite structure and semi-aromatic polyamide composite technology in polyester films, the problems of surface roughness and inorganic particles agglomeration of polyester films are solved, high dispersion and stability are achieved, and antistatic properties are improved, which is suitable for the base film of MLCC release films.
Patent Information
- Application Number
- CN202411013129.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-07-26
AI Technical Summary
When used in release films, the surface roughness of existing polyester films is difficult to reach Ra≤15nm, and inorganic particles are prone to agglomeration, resulting in a decrease in processing performance, and small molecules in the coating liquid are easily precipitated.
A PET film with three-layer composite structure adopts ABA, and combines the inorganic filler with semi-aromatic polyamide to form special masterbatches, and forms good dispersion and stability on the surface layer of the PET film. The surface roughness and anti-static coating liquid are further improved.
It effectively reduces the surface roughness of the film, improves the dispersion and stability of inorganic particles, avoids the risk of precipitation of inorganic particles, and improves the antistatic properties and applicability of the film.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyester films, in particular to a base film used for MLCC release films and a preparation method thereof. Background Art
[0002] At present, the polyester film used on the market is usually polyethylene terephthalate (PET), which is a colorless, transparent, glossy film with good mechanical properties, high hardness and toughness, excellent puncture resistance and friction resistance. Therefore, it is used in many fields such as electrical insulation film, capacitor film, release film, composite current collector film, polarizer protective film, packaging film, etc.
[0003] When used as a release film or protective film, the PET film needs to have a low surface roughness, a certain degree of anti-stickiness and surface smoothness. In response to such high-performance requirements, the current modification technology solutions for polyester films include adding nano-scale or micro-scale inorganic particles, such as silicon dioxide, calcium carbonate, etc., to its surface to reduce surface roughness; or coating the film surface with a coating containing micro-scale particles to improve the surface tension of the film. However, the current technical solutions for polyester films are still insufficient. The addition of inorganic particles requires controlling their size and addition amount, and the resulting surface roughness still cannot meet Ra≤15nm, and the inorganic particles are prone to agglomeration, resulting in decreased processing performance; and although the coating formed by coating can improve the surface tension, the coating liquid usually contains small molecular organic components, which are also prone to precipitation risks during subsequent processing. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention compounds inorganic fillers with semi-aromatic polyamides and adds them to the surface PET to form a PET film with an ABA three-layer composite structure. The inorganic particles on the film surface have good dispersion, high stability, and the surface roughness is effectively reduced. On the basis of the effective reduction of the roughness, a layer of antistatic coating liquid is first applied during the preparation of the base film, which can further improve the surface roughness and play an antistatic role.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a base film for an MLCC release film comprises the following steps:
[0007] S1. Mix the measured PET chips and special masterbatch and send them into the auxiliary extruder; put the pure PET chips into the crystallizer, pre-crystallize at 120-140°C for 15 minutes, and then send them into the drying tower for drying, and then send them into the main extruder after drying;
[0008] S2, adjust the temperature of the auxiliary extruder to 265-290°C, the temperature of the main extruder to 255-270°C, after melting, measure, extrude and filter;
[0009] S3, using the materials extruded by the auxiliary extruder as the upper and lower surface layers, and the materials extruded by the main extruder as the middle core layer, and making an ABA three-layer composite casting sheet through a multi-layer co-extrusion process;
[0010] S4, preheating the cast sheet at 65-90° C., and longitudinally stretching the sheet by 3-3.5 times at 90-110° C. to obtain a longitudinally stretched sheet;
[0011] S5, coating a layer of antistatic coating liquid on the upper and lower surfaces of the longitudinally stretched sheet by roller coating, then preheating at 90-120° C., and transversely stretching 3.5-4 times at 100-130° C.; after the stretching is completed, heat setting is performed, and then cooling, pulling and winding are performed to obtain;
[0012] The special masterbatch is prepared from 20-40wt% KH550 modified inorganic filler and 60-80wt% semi-aromatic polyamide. The semi-aromatic polyamide is dissolved in a mixed solvent of toluene and ethanol in a reaction bottle, and a catalyst LHMDS is added and mixed evenly. The KH550 modified inorganic filler is evenly dispersed in ethanol and then added to the reaction bottle, stirred at room temperature for 30-90 minutes, then quenched with sodium bicarbonate and filtered, the filter cake is washed with acetone and water and then dried, and extruded and granulated by an extruder.
[0013] Furthermore, the KH550 modified inorganic filler is obtained by placing a certain amount of inorganic particles in a 5wt% potassium hydroxide solution for activation treatment, then redispersing the treated inorganic particles in deionized water and adding an equal mass of KH550, stirring at 50°C for 24 hours, filtering, washing, drying and grinding; the inorganic particles are silicon dioxide.
[0014] Furthermore, the semi-aromatic polyamide is prepared from aromatic dibasic acid, aliphatic dibasic acid, siloxane-containing diamine monomer, aliphatic diamine and a hydroxyl-containing end-capping agent.
[0015] Furthermore, the aliphatic dibasic acid is selected from one of succinic acid, adipic acid, pimelic acid, glutaric acid, and malonic acid; and the aromatic dibasic acid is selected from 2-bromoterephthalic acid or 5-bromoisophthalic acid.
[0016] Furthermore, the siloxane-containing diamine monomer is aminopropyl-terminated polydimethylsiloxane with a molecular weight of 400 to 1000; the aliphatic diamine is selected from one of 1,2-diamino-2-methylpropane, 2,5-dimethyl-2,5-hexanediamine, dimethylpropylenediamine, hexamethylenediamine, and ethylenediamine.
[0017] Furthermore, the hydroxyl-containing capping agent is ethanolamine or o-hydroxyaniline.
[0018] Furthermore, the molar ratio of the aromatic dibasic acid, aliphatic dibasic acid, siloxane-containing diamine monomer, and aliphatic diamine is 3:2:1:4; and the amount of the hydroxyl-containing end-capping agent is 0.1 to 5 wt % of the total mass of the above four monomers.
[0019] Furthermore, the raw material usage ratio of the ABA three-layer structure is A layer: B layer: A layer = 10-20: 60-80: 10-20; the mass ratio of PET chips and special masterbatch in the A layer is 70-90: 10-30.
[0020] Furthermore, the antistatic coating liquid comprises the following components in parts by weight: 20-30 parts of waterborne epoxy resin, 2-6 parts of polythiophene, 1-3 parts of nonionic antistatic agent, 1-3 parts of compatibilizer, 5-15 parts of curing agent and the balance of water to make the total parts 100.
[0021] The present invention provides a base film used for MLCC release film, which is prepared by the preparation method as described above.
[0022] The present application prepares a special masterbatch formed by compounding a semi-aromatic polyamide as a functional polymer with an inorganic filler. The inorganic filler is a silica particle modified by a silane coupling agent, and an amino group is introduced on the surface of the inorganic particle. The semi-aromatic polyamide is formed by reacting an aromatic dibasic acid, an aliphatic dibasic acid (2-bromoterephthalic acid or 5-bromoisophthalic acid), a siloxane diamine monomer, an aliphatic diamine, and a hydroxyl-containing end-capping agent as raw materials. The silica particles are grafted onto the polymer chain to form a brush-like polymer by reacting the bromine in the polymer with the amino group in the inorganic filler. The terminal hydroxyl group can also produce a hydrogen bond effect with the amino group to promote the interaction and reaction between molecules, thereby improving the dispersibility of the inorganic particles. The functional polymer is mixed with PET to have good compatibility, and the technical problem of nanomaterials agglomerating and being difficult to disperse in polyester materials is well solved. At the same time, the inorganic particles compounded with the functional polymer are also difficult to precipitate from the surface of the film, thereby improving the stability of the surface energy of the film surface during processing and use.
[0023] Semi-aromatic polyamide has excellent mechanical properties and heat resistance. Introducing it into PET film can effectively improve the heat resistance of the material; combining it with inorganic fillers can effectively improve the impact strength of the film. PET mixed with special masterbatch is used as the outer layer of the intermediate core layer formed by pure PET slices, and synergistically with the intermediate core layer to improve the toughness of the film; the film surface is smooth and has low roughness. A layer of coating liquid is coated again on the longitudinal stretching sheet of the PET film with a three-layer composite structure. The resin material selected is epoxy resin, which has good compatibility with polyamide and good surface adhesion. Antistatic agent is added to the coating liquid to play an antistatic role.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adopts an ABA three-layer structure to prepare a PET film. First, a special masterbatch is added to PET as the base material in the A-layer structure, so that the film material has relatively excellent mechanical properties and heat resistance, and also has relatively low roughness, thereby avoiding the risk of precipitation of inorganic particles; in addition, a layer of antistatic coating liquid is coated on the longitudinally stretched sheet, and the coating liquid component has good compatibility with the semi-aromatic polyamide contained in the surface layer of the PET film. The coating layer is firmly bonded and cooperates with the surface layer, thereby further reducing the surface roughness and improving the antistatic performance of the film. The PET base film finally obtained is very suitable for use as a release film such as an MLCC release film base film. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0027] Embodiment: A method for preparing a base film for MLCC release film comprises the following steps:
[0028] S1. Mix the measured PET chips and special masterbatch and send them into the auxiliary extruder; put the pure PET chips into the crystallizer, pre-crystallize at 120-140°C for 15 minutes, and then send them into the drying tower for drying, and then send them into the main extruder after drying;
[0029] S2, adjust the temperature of the auxiliary extruder to 265-290°C, the temperature of the main extruder to 255-270°C, after melting, measure, extrude and filter;
[0030] S3, using the materials extruded by the auxiliary extruder as the upper and lower surface layers, and the materials extruded by the main extruder as the middle core layer, and making an ABA three-layer composite casting sheet through a multi-layer co-extrusion process;
[0031] S4, preheating the cast sheet at 65-90° C., and longitudinally stretching the sheet by 3-3.5 times at 90-110° C. to obtain a longitudinally stretched sheet;
[0032] S5, coating a layer of antistatic coating liquid on the upper and lower surfaces of the longitudinally stretched sheet by roller coating, then preheating at 90-120° C., and transversely stretching 3.5-4 times at 100-130° C.; after the stretching is completed, heat setting is performed, and then cooling, pulling and winding are performed to obtain;
[0033] The special masterbatch is prepared from 20-40wt% KH550 modified inorganic filler and 60-80wt% semi-aromatic polyamide. The semi-aromatic polyamide is dissolved in a mixed solvent of toluene and ethanol in a reaction bottle, and a catalyst LHMDS is added and mixed evenly. The KH550 modified inorganic filler is evenly dispersed in ethanol and then added to the reaction bottle, stirred at room temperature for 30-90 minutes, then quenched with sodium bicarbonate and filtered, the filter cake is washed with acetone and water and then dried, and extruded and granulated by an extruder.
[0034] Embodiment 1:
[0035] An ABA three-layer structure PET film is prepared according to the above process, wherein the raw material of layer A includes 70 parts of PET chips and 30 parts of special masterbatch; the raw material of layer B is PET chips; and the raw material usage ratio is layer A: layer B: layer A = 10:80:10.
[0036] The special masterbatch is prepared from 20wt% KH550 modified inorganic filler and 80wt% semi-aromatic polyamide. The semi-aromatic polyamide is dissolved in a mixed solvent of toluene and ethanol in a reaction bottle, and a catalyst LHMDS is added and mixed evenly. The KH550 modified inorganic filler is evenly dispersed in ethanol and then added to the reaction bottle, stirred at room temperature for 30 to 90 minutes, then quenched with sodium bicarbonate and filtered, the filter cake is washed with acetone and water and then dried, and extruded and granulated by an extruder to obtain the special masterbatch.
[0037] Furthermore, the KH550 modified inorganic filler is obtained by placing a certain amount of inorganic particles in a 5wt% potassium hydroxide solution for activation treatment, then redispersing the treated inorganic particles in deionized water and adding an equal mass of KH550, stirring at 50°C for 24 hours, filtering, washing, drying and grinding; the inorganic particles are silicon dioxide.
[0038] The semi-aromatic polyamide is prepared from aromatic dibasic acid, aliphatic dibasic acid, siloxane-containing diamine monomer, aliphatic diamine and a capping agent.
[0039] In an optional embodiment, the aliphatic dibasic acid is selected from one of succinic acid, adipic acid, pimelic acid, glutaric acid, and malonic acid; the aromatic dibasic acid is selected from 2-bromoterephthalic acid or 5-bromoisophthalic acid. The siloxane-containing diamine monomer is aminopropyl-terminated polydimethylsiloxane with a molecular weight of 400 to 1000; the aliphatic diamine is selected from one of 1,2-diamino-2-methylpropane, 2,5-dimethyl-2,5-hexanediamine, dimethylpropylenediamine, hexamethylenediamine, and ethylenediamine.
[0040] Specifically, in this embodiment, 2-bromoterephthalic acid, succinic acid, aminopropyl-terminated polydimethylsiloxane (1000), and ethylenediamine are used as raw materials, and each raw material is weighed according to a molar ratio of 3:2:1:4. 2-bromoterephthalic acid and succinic acid are pre-mixed and dissolved in toluene, and nitrogen is introduced. Then, hexamethylenediamine is added dropwise under mechanical stirring, and refluxed for 3 hours after the addition is completed; then, a toluene dilution containing aminopropyl-terminated polydimethylsiloxane is added dropwise, and refluxed for 2 hours after the addition is completed; finally, 1wt% of ethanolamine by weight of the raw material is added to react for 1-2 hours, and the resulting mixture is precipitated and washed with acetone and water, and dried to obtain a functional polymer.
[0041] The antistatic coating liquid comprises the following components in parts by weight: 30 parts of waterborne epoxy resin, 5 parts of polythiophene, 3 parts of nonionic antistatic agent, 2 parts of compatibilizer, 10 parts of curing agent and the balance of water to make the total parts 100.
[0042] Embodiment 2:
[0043] The same as Example 1, except that the ratio of raw materials used is A layer: B layer: A layer = 20:60:20.
[0044] Embodiment 3:
[0045] Same as Example 2, except that the A layer raw material includes 80 parts of PET chips and 20 parts of special masterbatch.
[0046] Embodiment 4:
[0047] Same as Example 2, except that the raw material of layer A includes 90 parts of PET chips and 10 parts of special masterbatch; and the raw material of layer B is PET chips.
[0048] The surface roughness, surface resistance and coating adhesion of the above base film were tested.
[0049] The base film prepared above was coated with a release agent offline to prepare a release film for MLCC (GB / T25256-2010). The release force was tested and the results are recorded in Table 1.
[0050] Table 1
[0051] Example 1 Example 2 Example 3 Example 4 Pure PET film Surface roughness Ra(nm) 10 7 8 12 27 Surface resistance(Ω) <![CDATA[7.1×10 10 ]]> <![CDATA[1.5×10 10 ]]> <![CDATA[3.4×10 10 ]]> <![CDATA[1.7×10 11 ]]> <![CDATA[10 14 ]]> Coating Adhesion Level 1 Level 0 Level 0 Level 1 / Residual bonding rate % 93.4 95.1 94.2 92.8 80.5
[0052] As can be seen from Table 1, the PET base film prepared in the present application has a relatively low surface roughness, good adhesion between the base film and the release agent, and a high residual adhesion rate of the release layer, and is suitable for use as a base film for MLCC release films.
[0053] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing a base film for MLCC release film, characterized in that: The steps include: S1. Mix the measured PET chips and special masterbatch and send them into the auxiliary extruder; put the pure PET chips into the crystallizer, pre-crystallize at 120-140 °C for 15 min, and then send them into the drying tower for drying, and then send them into the main extruder after drying; S2, adjust the temperature of the auxiliary extruder to 265~290℃, the temperature of the main extruder to 255~270℃, after melting, measure, extrude and filter; S3, using the materials extruded by the auxiliary extruder as the upper and lower surface layers, and the materials extruded by the main extruder as the middle core layer, and making an ABA three-layer composite casting sheet through a multi-layer co-extrusion process; S4, preheating the cast sheet at 65-90°C, and longitudinally stretching the sheet by 3-3.5 times at 90-110°C to obtain a longitudinally stretched sheet; S5, coating a layer of antistatic coating liquid on the upper and lower surfaces of the longitudinally stretched sheet by roller coating, then preheating at 90-120°C, and transversely stretching 3.5-4 times at 100-130°C; after stretching, heat setting, cooling, pulling and winding, and obtaining; The special masterbatch is prepared from 20-40wt% KH550 modified inorganic filler and 60-80wt% semi-aromatic polyamide. The semi-aromatic polyamide is dissolved in a mixed solvent of toluene and ethanol in a reaction bottle, and a catalyst LHMDS is added and mixed evenly. The KH550 modified inorganic filler is evenly dispersed in ethanol and then added to the reaction bottle, stirred at room temperature for 30-90 minutes, then quenched with sodium bicarbonate and filtered, the filter cake is washed with acetone and water and then dried, and extruded and granulated by an extruder to obtain the obtained product. The raw materials of the semi-aromatic polyamide include aromatic dibasic acid, aliphatic dibasic acid, siloxane-containing diamine monomer, aliphatic diamine and a hydroxyl-containing end-capping agent; The aromatic dibasic acid is selected from 2-bromoterephthalic acid or 5-bromoisophthalic acid.
2. The method for preparing a base film for MLCC release film according to claim 1, characterized in that: The KH550 modified inorganic filler is obtained by placing a certain amount of inorganic particles in a 5wt% potassium hydroxide solution for activation treatment, then redispersing the treated inorganic particles in deionized water and adding an equal mass of KH550, stirring at 50°C for 24 hours, filtering, washing, drying and grinding; the inorganic particles are silicon dioxide.
3. The method for preparing a base film for MLCC release film according to claim 1, characterized in that: The aliphatic dibasic acid is selected from one of succinic acid, adipic acid, pimelic acid, glutaric acid and malonic acid.
4. The method for preparing a base film for MLCC release film according to claim 1, characterized in that: The siloxane-containing diamine monomer is aminopropyl-terminated polydimethylsiloxane with a molecular weight of 400-1000; the aliphatic diamine is selected from one of 1,2-diamino-2-methylpropane, 2,5-dimethyl-2,5-hexanediamine, dimethylpropylenediamine, hexamethylenediamine, and ethylenediamine.
5. The method for preparing a base film for MLCC release film according to claim 1, characterized in that: The hydroxyl-containing end-capping agent is ethanolamine or o-hydroxyaniline.
6. The method for preparing a base film for MLCC release film according to claim 1, characterized in that: The molar ratio of the aromatic dibasic acid, the aliphatic dibasic acid, the siloxane-containing diamine monomer, and the aliphatic diamine is 3:2:1:4; the amount of the hydroxyl-containing end-capping agent is 0.1-5wt% of the total mass of the above four types of monomers.
7. The method for preparing a base film for MLCC release film according to claim 1, characterized in that: The raw material usage ratio of the ABA three-layer structure is A layer: B layer: A layer = 10-20: 60-80: 10-20; the mass ratio of PET chips and special masterbatch in the A layer is 70-90: 10-30.
8. The method for preparing a base film for MLCC release film according to claim 1, characterized in that: The antistatic coating liquid comprises the following components in parts by weight: 20-30 parts of waterborne epoxy resin, 2-6 parts of polythiophene, 1-3 parts of nonionic antistatic agent, 1-3 parts of compatibilizer, 5-15 parts of curing agent and the balance of water so that the total parts are 100.
9. A base film for MLCC release film obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method for polyamide composite nanofiltration membrane containing amino-modified nanoparticles
CN107583469A
Five-layer polyester film for dry film resist and preparation method thereof
CN114083865A
Co-polyester packaging resins prepared without solid-state polymerization, a method for processing the co-polyester resins with reduced viscosity change and containers and other articles prepared by the process
US20070248778A1